Positive Predictive Value of Abnormal Cardiotocography Trace During Labour for Poor Fetal Outcome (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the positive predictive value of abnormal cardiotocography (CTG) trace during labour for poor fetal outcome.Study design: Cross sectionalDuration of Study: Six months from 24 ‐05‐2011 till 24‐12‐2011Setting: Study was carried out in the department of Obstetrics & Gynaecology, Sir Ganga Ram Hospital, Lahore.Results: Majority of the patients i.e. 43.46%(n=113) were between 20‐25 years of age, mean & sd was calculated as 24.25+ 5.21 years, frequency of poor fetal outcome was recorded in 31.92%(n=83), positive predictive value of abnormal cardiotocography (CTG) trace during labour for poor fetal outcome was recorded which shows 29.23%(n=76) true positive, 7.31%(n=19) false positive, 2.69%(n=7) had false negative while true negative was recorded in 60.77%(n=158), sensitivity, specificity, positive predictive value, negative predictive value & diagnostic accuracy was recorded as 91.57%, 89.27%, 80%, 95.67% and 90% respectively.Conclusion: Abnormal cardiotocography trace during labour is an effective & reliable tool for prediction of poor fetal outcome.
Keywords: Abnormal CTG trace, during labour, diagnostic accuracy, poor fetal outcome